Réponses

2013-05-28T18:26:10+02:00

Exercice 4 : -4(3x-9)+(6-7x)

                    = -4*3x+(-4)*9+(-4)*6-(-4)*7x

                    = 12x+ (-36)+(-24)+28x

                    =12x - 36 - 24 + 28x

                    = (12+28)x -(36-24)

                    = 40x -  12.

 

                     (-7x+3)(5+4x)

                     = -7x*5+(-7x)*4x+3*5+3*4x

                      = -35+28x+15+12x

                      = (28+12)x - (35+15)

                      = 41x - 50.

 

                      (-7x+3)(-3-7x)

                      = -7x*-3+(-7x)*-7x+3*(-3)+3*(-7x)

                      = 21x+ 49x+ (-9)+ (-21x)

                      = 21x+49x-9-21x

                      =(21+49+21)x -9

                       =91x-9.